Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Keterampilan Sosial Dan Prestasi Belajar Siswa Kelas V SD - Rahayuningtyas, Dian Ikawati (Jurnal Pancar, 2018)
This research aims to reveal the difference between the effect of? the Guided Inquiry Learning??? Model and the expository learning model on: (1) the social skill, and (2) the ?social study achievement of the year V? students of elementary schools in Ki Hajar Dewantara Group, Cilongok. This? research? was a quasi? experiement. The? design ?which ?was used vvas pretest-posttest? control group design with two experimental groups taught by using the guided inquiry model and? expository model respectively. The research population was all of year V students of elernantary???? schools ?in Ki Hajar Dewantara group, Cilongok. The sample consisting of class VA as the experimental?? class I class VB Kalisari Elementary schools as the experimen class II and year TV students of Cikidang 2 Elementary School as the control class was established by using the cluster random sampling technique. The instrument used was a test, to discover the social skill and the social study achievement before and? after the treatment. The realibility of? the instrument was catagorized as good at the value of 0.7 Cronbach's Alpa .The data analysis used the Paired Sample T-test and Independent Sample Titest supported by SPSS 16.0 for Windows. The results of the research showed that: (1) there is a different effect between thee guided inquiry?? model and the expository learning model on the social skill at the significance level of? 0,000 < 0.05, and (2) there is a different effect between the guided inquiry model and the expository learning??? model on the social study achievement at the significance level of 0.000? < 0.05.